PENGARUH KOMPETENSI DAN KINERJA GURU TERHADAP HASIL BELAJAR SISWA DI MADRASAH TSANAWIYAH MIFTAHUL ULUM DENPASAR BALI TAHUN AJARAN 2024/205 - HOTIJAH; Ni Luh Putu Yesy Anggreni; Luh De Liska (Arthaniti Studies, 2025)
This study aims to determine the effect of teacher competence on student learning outcomes at Madrasah Tsanawiyah Miftahul Ulum Denpasar Bali in the 2024/2025 Academic Year. The effect of teacher performance on student learning outcomes at Madrasah Tsanawiyah Miftahul Ulum Denpasar Bali in the 2024/2025 Academic Year. The effect of teacher competence and performance together on student learning outcomes at Madrasah Tsanawiyah Miftahul Ulum Denpasar Bali in the 2024/2025 Academic Year. This study uses a quantitative approach with data collection techniques of observation, interviews, documentation and questionnaires which took 100 respondents/students. The results of this study indicate that (1) There is a significant effect of competence on student learning outcomes at MTs. Miftahul Ulum Denpasar. This is proven by the t-value of 3.818 which means it is greater than the t-table of 1.984 (3.818 > 1.984) meaning H0 is rejected and Ha is accepted, which means teacher competence (X1) has a significant partial influence on student learning outcomes (Y) at MTs. Miftahul Ulum Denpasar. (2) There is a significant influence of teacher performance on student learning outcomes at MTs. Miftahul Ulum Denpasar. This is proven by the t-value of 16.250 which means it is greater than the t-table of 1.984 (16.250 > 1.984) which is in the H0 rejection area, meaning H0 is rejected and Ha is accepted, which means teacher performance (X2) has a significant partial influence on student learning outcomes (Y) at MTs. Miftahul Ulum Denpasar. (3) There is a significant influence of teacher competence and performance together on student learning outcomes at MTs. Miftahul Ulum Denpasar. This is proven by the value obtained by the F count value of 95.210 > from F table, 95.210 > 3.09 so that H0 is rejected and Ha is accepted. The results of the determination coefficient show that the Adjusted R Square is 0.766, which means that 76.6% of the variation in learning outcomes (Y) is influenced by teacher competence (X1) and teacher performance (X2) while the remaining 24.4% is influenced by other factors that are not included in the research model.